KAJIAN KISAH-KISAH DALAM AL-QUR’AN (tinjauan historis dalam memahami al-Qur’an) - Abd Haris (Universitas Islam Madura, 2018)
Story is a learning method turned out to have its own charm, can touch the feelings, psychological and thinking power of a person. The story has an invaluable educational function in a process of planting Islamic values and teachings. Al- Qur'an is not only discusses monotheism matters related to ubudiyah mankind, but also related to historical problems that occur in the preceding peoples, so that the human can take 'ibrah for the sake of improving the life to come on the ext future. In terminology, the word”story” is derived from the Arabic word, qassas. The word qassa s itself is the plural of the word qisas which is means the trail or tracing the former or the story (the story). As for the various stories in Al-Qur'an can be seen from several sides, point od view from the time of the event side, then also seen in material term or content of the story is described in Al-Qur'an. While the actor techniques in the Qur'an are art, religious forms and advice form. The purpose is to provide way of life and references to take lessons from some of the stories described in Al- Qur'an.